Evaluation of Saline Sonohysterography Findings in Patients with Breast Cancer Receiving Tamoxifen Adjuvant Therapy - Rahmani, Maryam; Farmanbordar, Leila; Omranipour, Ramesh; Malek, Mahrooz; Zand, Sanaz (Archives of Breast Cancer, 2016)
Background: Transvaginal ultrasound is one of the most common means to examine endometrial cavity lesions although its negative results are more valuable. Saline sonohysterography can reduce the number of false negative rates of endometrial lesions diagnoses in Tamoxifen consumers. The Objective of this study was to determine the diagnostic values of saline infusion sonohysterography (SIS) and hysteroscopy as gold standard in diagnosis of endometrial pathologies in patients with breast cancer receiving adjuvant therapy with Tamoxifen for at least 6 months. Methods: This cross-sectional study was conducted on 40 patients with breast cancer who were treated with for at least 6 months and referred by the gynecologist for evaluation. Age, duration of Tamoxifen use and symptoms were recorded. Patients were examined by saline sonohysterography. Ultrasonic endometrial findings were recorded. Patients with positive findings were referred for hysteroscopy and biopsy was taken for pathologic examination. Then we compared the results. Results: In total, 40 patients with a mean age of 46.5±7.81 years and mean duration of Tamoxifen treatment 18.4 ±13.98 months were included. There were intrauterine lesions in 22 patients and they did not undergo hysteroscopy. For others, 9 patients with endometrial polyp (21.41%), 3 patients with endometrial hyperplasia (7.14%) were found. The accuracy of SSH in diagnosing endometrial polyp, endometrial hyperplasia and submucosal fibroma were 87.5%, 92.5% ,97.5%, respectively. Conclusions: Saline sonohysterography is a viable option for screening of the patients instead of endometrial biopsy as it has great negative predictive value. Sonohysterography is easy, non-invasive, inexpensive and has great accuracy.